THE PLAY OF MONOLOGUE PUTU WIJAYA; CREATIVE PROCESS AND PERIOD OF WRITING - ENRICO ALAMO (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2020)
Putu Wijaya is one of the most important Indonesian playwrights in writing, both; short stories, novels, drama scripts, and even monologue scripts. At the moment the manuscript is published, published 118 titles published in the book "100 Monologue Works: Putu Wijaya". On the sidelines of his recovery, Putu Wijaya who was plagued by a brain hemorrhage due to a mild stroke was still an actor performing a monologue script titled "OH". Being born as one of the Balinese aristocracies did not make Putu Wijaya remain in his caste, even the days were filled with authorship, he never gave up. Do not want the gnawing disease to stop the field being cultivated. Long before the Japanese occupation of Indonesia, Putu Wijaya's tenacity was seen in defending the world of authorship. This research on Putu Wijaya is grouped based on creativity and the periodization of Putu Wijaya from its inception